Electrodeposition of Nickel in metallic materials in disuse (Technological Innovations Journal, 2022)
This study carried out the electrodeposition of nickel in used iron metallic materials, which was called cathode to verify the adequate conditions, these processes were carried out in the laboratories of the Faculty of Metallurgical Engineering of the Altiplano National University, the investigation sought find the parameters of temperature, humidity, pH to conditions of Puno department. Such data is different from the electrodeposition in the regions of the coast and the Peruvian jungle, for which the objective of verifying if the electrodeposition process will be able to satisfy the expected expectations in the coating of metals through the watt’s methodology was raised. The number of tests was constituted by the electrodeposition of 20 half-inch tubes previously subjected to a washing process and prepared for their electrolytic bath, in a number of four units every 10 minutes. To verify quality control, weight differences were carried out. Obtaining the results of appropriating voltage of 2.0V, amperage of 1.5A and a time of 10 minutes are the ideal parameters obtained in the nickel electrodeposition process at environmental conditions of the high plateau region.